Attitudes and Preferences of Kosovar Consumer Segments Toward Quality Attributes of Milk and Dairy Products. Issue 4 (1st October 2016) - Haas, Rainer; Canavari, Maurizio; Imami, Drini; Gjonbalaj, Mujë; Gjokaj, Ekrem; Zvyagintsev, Dmitry
ABSTRACT: The dairy market is one of the fastest growing agri-food sectors in Kosovo, yet the farm structure is fragmented. The level of productivity is lower compared with European Union levels and shows potential for improvements. The consumption of dairy products is expected to rise due to income growth and segmentation of consumers that would reflect different preferences for low-fat or zero-fat products, products with natural additives, and so on. On the market level, a significant share of the consumed milk and dairy products is imported. This study aims to better understand attitudes and preferences of Kosovar consumer segments toward milk and dairy products. A quantitative survey with 300 consumers was conducted in major Kosovo cities. Applying a reduced version of the Food Related Lifestyle instrument identified three distinct consumer segments: the conservative consumer segment, the socially oriented foodie, and the information-seeking eco-consumer. The latter two segments are especially open to trying new food products and actively search information about food. All three consumer segments show strong consumer patriotism by believing that domestic milk and cheese are safer than imported products and are of higher quality. This indicates the strong market potential for dairy farmers and companies in the Kosovo, which should develop new food products having these segments in mind. The authors explore the strategies that farmers and companies should use to better target these consumer groups and gain greater access to desirable segments.